2022
DOI: 10.3390/jcm11102701
|View full text |Cite
|
Sign up to set email alerts
|

Is MRPI 2.0 More Useful than MRPI and M/P Ratio in Differential Diagnosis of PSP-P with Other Atypical Parkinsonisms?

Abstract: Differential diagnosis of progressive supranuclear palsy remains difficult, especially when it comes to the parkinsonism predominant type (PSP-P), which has a more favorable clinical course. In this entity, especially during the advanced stages, significant clinical overlaps with other tauopathic parkinsonian syndromes and multiple system atrophy (MSA) can be observed. Among the available additional diagnostic methods in every-day use, magnetic resonance imaging (MRI) focused specifically on the evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…PSP-P and MSA-P may manifest clinical features which overlap with Parkinsonian syndrome, with a possibly moderate response to levodopa treatment, as well as preserved or benignly deteriorated cognitive abilities. The neuroimaging parameters introduced as Magnetic Resonance Parkinsonism Index 2.0 (MRPI 2.0) to examine PSP-P seem to be feasible in its differentiation from PD, but are not sufficiently specific in comparison to MSA-P [ 5 , 7 , 8 , 9 ]. Previous work by this research group found that mesencephalon/pons ratio and MRPI may be beneficial in the neuroimaging differentiation of PSP-P and MSA-P [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PSP-P and MSA-P may manifest clinical features which overlap with Parkinsonian syndrome, with a possibly moderate response to levodopa treatment, as well as preserved or benignly deteriorated cognitive abilities. The neuroimaging parameters introduced as Magnetic Resonance Parkinsonism Index 2.0 (MRPI 2.0) to examine PSP-P seem to be feasible in its differentiation from PD, but are not sufficiently specific in comparison to MSA-P [ 5 , 7 , 8 , 9 ]. Previous work by this research group found that mesencephalon/pons ratio and MRPI may be beneficial in the neuroimaging differentiation of PSP-P and MSA-P [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The neuroimaging parameters introduced as Magnetic Resonance Parkinsonism Index 2.0 (MRPI 2.0) to examine PSP-P seem to be feasible in its differentiation from PD, but are not sufficiently specific in comparison to MSA-P [ 5 , 7 , 8 , 9 ]. Previous work by this research group found that mesencephalon/pons ratio and MRPI may be beneficial in the neuroimaging differentiation of PSP-P and MSA-P [ 5 ]. The role of MRPI in the examination of PSP-P and MSA-P was also found to be distinguishing the diseases in a separate study [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few data also exist on the differential diagnosis between PSP and cortico-basal degeneration (CBS). The midbrain is generally more atrophic in PSP-RS than in CBS at a group level [ 71 ], while no differences were found between PSP-P and CBS in one study [ 70 ]. This overlap can be partially explained because the clinical diagnosis of CBS is associated with a bucket of different underlying pathologies, including CBD, Alzheimer’s disease, TDP-43 pathology but also PSP pathology in a significant number of cases [ 67 , 72 ], thus making the pathological confirmation absolutely needed in this context.…”
Section: Mr Planimetric Biomarkersmentioning
confidence: 99%
“…These planimetric brainstem measurements yielded good diagnostic accuracy for the discrimination of PSP from MSA, with the M/P area ratio showing higher sensitivity and the MRPI showing higher specificity (MRPI: 79.2% pooled sensitivity and 91.2% pooled specificity; M/P: 84.1% pooled sensitivity and 89.2% pooled specificity). Only one study [70] investigated the diagnostic performance of planimetric biomarkers in distinguishing the PSP-P subtype from MSA-P, showing some overlap between groups. Further studies are needed to better elucidate the role of MRPI and MRPI 2.0 in distinguishing PSP-P from MSA-P. At the bottom, there is the probability of having PSP-RS rather than PD for each automated MRPI value (C) and the probability of having PSP-P rather than PD for each automated MRPI 2.0 value (D), obtained using logistic regression models balancing the number of PD and PSP patients.…”
Section: Role Of Planimetric Biomarkers In Distinguishing Psp From Ot...mentioning
confidence: 99%